The Effect of Memory Game on Reading Comprehension Skill of Eighth Grade Students at UPTD SMP Negeri 3 Mandrehe - Linda Mariani Gulo; Yaredi Waruwu; Afore Tahir Harefa; Riswan Zega (Badan Penerbit STIEPARI Press, 2025)
This study aims to examine the effect of using a memory game as a teaching medium on the reading comprehension skills of eighth-grade students at UPTD SMP Negeri 3 Mandrehe. A quasi-experimental, nonequivalent pretest-posttest design was implemented with 60 purposively selected students, who were divided into two groups: a control group and an experimental group. The control group received conventional teaching methods, while the experimental group was taught using a memory game from the Interacty platform. Data were collected through multiple-choice reading comprehension tests administered before and after the treatment. The results were analyzed using paired and independent sample t-tests as well as N-Gain calculations to measure the improvement in reading comprehension skills. The analysis revealed that the experimental group showed a significantly higher improvement in reading comprehension, with an N-Gain score of 0.792 (high) compared to the control group’s 0.244 (low). The findings indicate that memory games effectively enhance vocabulary retention, increase student motivation, improve focus, and create an engaging classroom atmosphere. By incorporating memory games, students became more actively involved in learning, which contributed to improved reading comprehension skills. The study concludes that memory games are a valuable tool for improving reading comprehension and fostering an enjoyable and meaningful learning experience. Therefore, it is recommended that memory games be integrated into junior high school English instruction as an innovative teaching strategy to enhance students’ reading skills. The research highlights the potential of interactive and engaging methods in facilitating language learning, thus suggesting that educators should consider adopting such approaches to improve educational outcomes in reading comprehension.